Preparation method and application of three-dimensional reticular Rh / Ni (OH) 2 nanowire composite material

By introducing Rh into nickel-based hydroxide, a three-dimensional network Rh/Ni(OH)2 nanowire composite material was prepared, which solved the problem of poor hydrogen evolution activity of nickel-based hydroxide in alkaline media, and achieved the Low energy consumption and efficient electrocatalytic hydrogen production, and significantly improve the stability of the catalyst.

CN119465275APending Publication Date: 2025-02-18JIANGSU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411672461.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, nickel-based hydroxides have poor hydrogen evolution activity in alkaline media, and commercial catalysts have problems of high cost and poor stability, which limits the widespread application of electrocatalytic water decomposition to hydrogen production.

Method used

By introducing Rh into nickel-based hydroxide, a three-dimensional network Rh/Ni(OH)2 nanowire composite was prepared, and the material was synthesized by hydrothermal reaction method, which simplified the preparation process and improved the stability of the material.

Benefits of technology

It has achieved low energy consumption and high efficiency electrocatalytic hydrogen production, significantly improved the hydrogen evolution activity of nickel-based hydroxides, and the stability of the catalyst reaches more than 90%, which is economical.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465275A_ABST
    Figure CN119465275A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of material science, and discloses a preparation method and application of a three-dimensional reticular Rh / Ni (OH) 2 nanowire composite material. The preparation method comprises the following steps: 1) adding nickel salt and urea into water in proportion, and carrying out ultrasonic treatment to obtain a uniform clear transparent solution; (2) transferring the clear and transparent solution into a lining of a polytetrafluoroethylene reaction kettle, adding a rhodium salt solution, and stirring to obtain a mixture solution; and (3) putting cleaned foam nickel with a certain size into the mixture solution, sealing in a reaction kettle, carrying out hydrothermal reaction for a period of time, taking out the reacted foam nickel after the reaction is finished, and washing and drying to obtain the Rh / Ni (OH) 2 nanowire mesh composite material. According to the invention, efficient and stable electro-catalysis water decomposition hydrogen production is realized, the problems of poor intrinsic activity of nickel-based hydroxide in the catalytic hydrogen evolution process, low activity in precious metal alkaline electrolyte and poor stability are solved, and efficient electro-catalysis water decomposition hydrogen production is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a three-dimensional mesh Rh / Ni(OH)2 nanowire composite material, belonging to the field of material science. Background Art

[0002] As a clean renewable energy, hydrogen energy is considered to be a green energy with the potential to replace fossil fuels due to its high energy density and zero carbon dioxide emissions. At present, the main ways to produce hydrogen energy include natural gas reforming, coal gasification and water splitting. Among them, water splitting using electrochemical technology is considered to be the most environmentally friendly, simplest and most effective way to produce hydrogen energy. At present, Pt / C is considered to be a commercial catalyst for hydrogen evolution, while IrOx / RuOx is the benchmark for oxygen evolution reaction. However, in alkaline media, the reaction rate of hydrogen evolution reaction on Pt electrode is much lower than that in acidic media due to the need for an additional water dissociation process in alkaline media. In addition, problems such as high cost, insufficient reserves and poor stability have greatly hindered the large-scale application of commercial catalysts in water splitting. Therefore, the development of cost-effective and stable catalysts to replace Pt / C and IrOx / RuOx is of great significance for the widespread application of electrocatalytic water splitting to produce hydrogen.

[0003] Nickel-based hydroxides are a class of promising electrocatalytic water splitting catalysts because they exhibit good stability, outstanding oxygen evolution catalytic activity and abundant reserves in alkaline media. However, due to poor conductivity and weak hydrogen atom adsorption capacity, nickel-based hydroxides exhibit poor intrinsic activity in the hydrogen evolution process. At present, the main strategies to improve the hydrogen evolution activity of nickel-based hydroxides include: regulation of geometric structure and elemental composition; heteroatom doping; defect engineering and other methods. Among them, geometric structure and defect engineering can optimize the electrode surface structure so that more activity can be exposed. However, morphology regulation and defect engineering usually involve cumbersome preparation processes and difficult long-term maintenance of structures. Heteroatom doping is easier to achieve through co-deposition. Although the doping of most transition metals greatly improves the oxygen evolution activity of nickel-based hydroxides, the improvement in hydrogen evolution activity is not obvious. Therefore, it is urgent to develop efficient strategies to improve the electrocatalytic activity of nickel-based hydroxide materials.

[0004] Precious metal doping has become a promising strategy for improving transition metal-based compounds by optimizing the coordination environment and the adsorption energy of intermediates. At present, the commonly used and main types of precious metals are Ru, Pt, and Ir, while the research on Rh is relatively small. It has been reported that the introduction of Rh into NiFe hydrotalcite can increase the dissociation rate of water, which is beneficial to the alkaline hydrogen evolution reaction. At the same time, the strong adsorption of Rh on hydrogen evolution intermediates balances the weak adsorption of transition metals on H, significantly improving the electrolytic water splitting performance of transition metal-based materials). The introduction of Rh into nickel-based hydroxides is expected to improve the electrocatalytic water splitting activity of nickel-based hydroxides, but there are few reports on material design and electrocatalytic water splitting.

[0005] In summary, how to introduce Rh into nickel-based hydroxide: combining nickel-based hydroxide with precious metal Rh to develop high-activity, low-precious metal loading Rh / Ni(OH)2 has become an urgent problem to be solved.

[0006] Nickel hydroxide has poor conductivity and poor adsorption capacity of hydrogen atom intermediates, resulting in poor intrinsic activity of hydrogen evolution; while commercial Pt / C in alkaline systems has problems such as poor catalytic water dissociation ability and poor stability.

[0007] At present, the main method to improve the performance of nickel hydroxide electrolysis is through transition metal doping strategy, but the introduction of transition metals mainly regulates the activity of the anode oxygen evolution process, and the activity of the cathode hydrogen evolution end needs to be further improved;

[0008] Precious metal doping can significantly regulate the adsorption / desorption energy of intermediates in transition metal-based compounds during the catalytic process. However, current research is mostly focused on several precious metals such as Pt, Ir, and Ru, and there is little research on the regulation mechanism of Rh. Summary of the invention

[0009] In view of the problems existing in the prior art, the present invention provides a preparation and application of a three-dimensional network Rh / Ni(OH)2 nanowire composite material, realizes the application of efficient water electrolysis to hydrogen production by nickel hydroxide, and provides a new idea for the production of green hydrogen using transition metal-based materials as catalysts.

[0010] The first object of the present invention is to provide a method for preparing a Rh / Ni(OH)2 nanowire network composite material, comprising the following steps:

[0011] (1) adding nickel salt and urea in a certain proportion into water and ultrasonically obtaining a uniform clear and transparent solution;

[0012] (2) transferring the clear and transparent solution to a polytetrafluoroethylene-lined reactor, adding a certain volume of rhodium salt solution, and stirring to obtain a mixture solution;

[0013] (3) The washed nickel foam of a certain size is placed into the above-mentioned mixture solution and sealed in a reaction kettle, and a hydrothermal reaction is carried out at a certain temperature for a period of time. After the reaction is completed, the nickel foam is taken out, washed and dried to obtain a Rh / Ni(OH)2 nanowire network composite material.

[0014] In step (1), the nickel salt refers to one of nickel chloride, nickel nitrate or nickel sulfate.

[0015] In step (2), the rhodium salt refers to one of rhodium chloride, rhodium chloride hydrate, or rhodium nitrate.

[0016] In steps (1) and (2), the usage ratio of nickel salt, urea and rhodium salt is: 0.291-2.910 g: 0.601-6.010 g: 0.5-25 mg.

[0017] In step (2), the concentration of the rhodium salt solution is 10-100 mg / mL.

[0018] In step (3), the size of the nickel foam is 1-3 mm in thickness and 1 cm×2 cm-4 cm×5 cm in area.

[0019] In step (3), the temperature of the hydrothermal reaction is 90-150° C., and the reaction time is 6-24 hours.

[0020] In step (3), washing is performed with water.

[0021] In step (3), drying is performed at a temperature of 60°C.

[0022] The second objective of the present invention is to prepare a self-supporting three-dimensional network Rh / Ni(OH)2 nanowire composite material using the method described in the present invention.

[0023] The third object of the present invention is to use the Rh / Ni(OH)2 nanowire network composite material prepared by the present invention for electrocatalytic water decomposition to produce hydrogen.

[0024] The electrocatalytic water splitting refers to the electrolysis of water in a 1 mol / L KOH aqueous solution.

[0025] The beneficial effects of the present invention are:

[0026] (1) Low energy consumption and efficient electrocatalytic hydrogen production are achieved:

[0027] In the field of electrocatalytic water splitting, transition metal hydroxides have poor intrinsic hydrogen evolution activity and low hydrogen production efficiency due to their poor hydrogen absorption and desorption capabilities, which increases energy consumption in the process of electrolytic water splitting and lacks economic benefits, and often has a very low resource utilization rate. The present invention explores the performance characteristics of precious metal Rh and nickel hydroxide to prepare a new material with high efficiency and stability - a three-dimensional network Rh / Ni(OH)2 nanowire composite material.

[0028] (2) Solved the problem of poor catalytic stability of precious metals in commercial catalysts:

[0029] The three-dimensional network Rh / Ni(OH)2 nanowire composite material provided by the present invention has a stable and efficient electrocatalytic water decomposition ability; the three-dimensional network Rh / Ni(OH)2 nanowire composite material is used as the anode and cathode of water electrolysis, and in a 1.0 mol / L KOH solution, only 68 mV overpotential is required to drive 10 mA / cm 2 The hydrogen evolution reaction was driven by a current density of 50 mA / cm and a 350 mV overpotential. 2 The catalytic stability of the oxygen evolution reaction at a current density of more than 10 hours reached more than 90%.

[0030] (3) Simple operation and technical process:

[0031] The catalytic material prepared by the present invention grows on a nickel foam substrate and can be directly used as an electrode. Compared with commercial Pt / C and RuO2, no additional electrode coating process is required, which simplifies the electrode preparation process. At the same time, the bonding force between the self-supporting material and the substrate is higher than the bonding force between the catalyst and the substrate bonded by a binder.

[0032] (4) Economic benefits:

[0033] Compared with undoped nickel hydroxide, the Rh / Ni(OH)2 nanowire catalyst significantly reduces the overpotential of hydrogen and oxygen evolution, thereby reducing the electrolytic cell pressure, reducing the reaction energy consumption, and is more economical and practical. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a scanning electron microscope image of the Rh / Ni(OH)2 nanowire network material in Example 1.

[0035] Figure 2 This is a structural diagram of the Rh / Ni(OH)2 nanowire network material in Example 1, where PDF#14-0117 is a β-Ni(OH)2 PDF card.

[0036] Figure 3 This is the hydrogen evolution activity of the Rh / Ni(OH)2 nanowire mesh material electrode in Example 1.

[0037] Figure 4 This is the oxygen evolution activity of the Rh / Ni(OH)2 nanowire mesh material electrode in Example 1. DETAILED DESCRIPTION

[0038] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.

[0039] Test method:

[0040] Morphology test:

[0041] The field emission scanning electron microscope was purchased from FEI Company, USA.

[0042] Performance measurement:

[0043] CHI electrochemical workstation was purchased from Shanghai Chenhua Instrument Co., Ltd.

[0044] The raw materials used in the examples are:

[0045] Nickel source: nickel chloride hexahydrate and nickel nitrate hexahydrate, purchased from Sinopharm Group.

[0046] Urea: purchased from Sinopharm Group

[0047] Nickel foam: 1.5 mm thick, purchased from Lizhiyuan Technology Co., Ltd.

[0048] Commercial Pt / C: 10 wt %, purchased from Suzhou Shengernuo Technology Co., Ltd.

[0049] Commercial RuO2: purity 99.95%, purchased from Adamas Beta (Shanghai) Chemical Reagent Co., Ltd.

[0050] The solutions involved in the embodiments and comparative examples without specifying the solvent are water as the solvent, and the wt% involved without specifying the meaning refers to the mass percentage.

[0051] Example 1

[0052] A preparation and application of a Rh / Ni(OH)2 nanowire mesh composite material comprises the following steps:

[0053] (1) Dissolve 0.291 g nickel nitrate and 0.601 g urea in 30 mL deionized water and ultrasonicate to obtain a uniform green clear solution;

[0054] (2) transferring the clear transparent solution to a 50 mL polytetrafluoroethylene liner reactor, adding 150 μL of a 50 mg / mL rhodium chloride hydrate solution, and stirring to obtain a mixture solution;

[0055] (4) 3×2cm 2The nickel foam was put into the above mixture solution, placed in a 50 mL reactor, sealed and subjected to hydrothermal reaction at 120 °C for 10 hours. The nickel foam after reaction was taken out, washed and dried to obtain a Rh / Ni(OH)2 nanowire mesh composite material with the morphology as shown in FIG. Figure 1 As shown, the diameter of the nanowires is about 15 nm, and the nanowires are interwoven into a nano-network morphology. Figure 2 As shown, the positions at 33.06°, 38.5°, 59.1° and 62.7° correspond to the (100), (101), (110) and (111) crystal planes of β-phase Ni(OH)2, respectively. The introduction of rhodium does not significantly change the β-phase structure of nickel hydroxide.

[0056] The method for electrocatalytic water decomposition using the three-dimensional network Rh / Ni(OH)2 nanowire composite material prepared above is as follows:

[0057] A 1cm×1.2cm Rh / Ni(OH)2 nanowire composite material was cut and clamped into an electrode clamp as a working electrode. A carbon rod was used as a counter electrode, mercury / mercuric oxide was used as a reference electrode, and a 1mol / LKOH solution was used as an electrolyte. The hydrogen evolution catalytic activity and oxygen evolution catalytic activity of the catalyst were tested in the anode voltage region and the cathode voltage region, respectively.

[0058] The test results are as follows:

[0059] like Figure 3 For the hydrogen evolution reaction, an overpotential of 68 mV is required to achieve a catalytic charge of 10 mA / cm 2 The hydrogen production current density is

[0060] like Figure 4 For the oxygen evolution reaction, an overpotential of 350 mV is required to drive the catalyst to 50 mA / cm 2 The oxygen production current density.

[0061] Comparative Example 1

[0062] Commercial Pt / C and RuO2 were used to catalyze the water decomposition, hydrogen evolution and oxygen evolution reactions, respectively, as follows:

[0063] 5 mg of commercial Pt / C was dissolved in 1 mL of ethanol, 50 μL of 5 wt% Nafion was added as a binder, and the mixture was mixed to obtain a slurry. 200 μL of the slurry was applied to a 1 cm × 1.2 cm nickel foam substrate, and the commercial Pt / C electrode was obtained after drying. 5 mg of commercial RuO2 was dissolved in 1 mL of ethanol, 50 μL of 5 wt% Nafion was added as a binder, and the mixture was mixed to obtain a slurry. 200 μL of the slurry was applied to a 1 cm × 1.2 cm nickel foam substrate, and the commercial RuO2 electrode was obtained after drying. The commercial Pt / C electrode was used as the working electrode, and the other electrodes were the same as those in Example 1. The hydrogen evolution activity of the commercial Pt / C electrode was tested in the hydrogen evolution potential region. The commercial RuO2 electrode was used as the working electrode, and the other electrodes were the same as those in Example 1. The oxygen evolution activity of the commercial RuO2 electrode was tested in the oxygen evolution potential region.

[0064] The Rh / Ni(OH)2 nanowire composite material in Example 1 was replaced with commercial Pt / C and RuO2, and the other conditions or parameters were consistent with those in Comparative Example 1, and the electrocatalytic water decomposition performance test was carried out.

[0065] The test results are as follows:

[0066] like Figure 3 For the hydrogen evolution reaction, the commercial Pt / C electrode requires an overpotential of 57 mV to achieve a catalytic reaction of 10 mA / cm 2 The hydrogen production current density is

[0067] like Figure 4 For the oxygen evolution reaction, the commercial RuO2 electrode requires an overpotential of 450 mV to drive the catalytic reaction to 50 mA / cm 2 The oxygen production current density.

[0068] Comparative Example 2

[0069] A method for preparing a self-supporting β-phase Ni(OH)2 nanowire comprises the following steps:

[0070] (1) Dissolve 0.29 g nickel nitrate and 0.6 g urea in 30 mL deionized water and ultrasonicate to obtain a uniform green clear solution;

[0071] (2) Transfer the clear solution into a 50 mL polytetrafluoroethylene-lined reactor;

[0072] (4) 3×2cm 2 The nickel foam is put into the above mixture solution, placed in a 50mL reactor, sealed and subjected to hydrothermal reaction at 120°C for 10 hours. The nickel foam after reaction is taken out, washed and dried to obtain Ni(OH)2 nanowire material. Figure 2As shown, the angles at 33.06°, 38.5°, 59.1° and 62.7° correspond to the β-phase Ni(OH)2(100), (101), (110) and (111) crystal planes, respectively.

[0073] The Rh / Ni(OH)2 nanowire composite material in Example 1 was replaced with Ni(OH)2 nanowires, and other conditions or parameters were consistent with those in Comparative Example 1, and the electrocatalytic water decomposition performance test was carried out.

[0074] The test results are as follows:

[0075] like Figure 3 For the hydrogen evolution reaction, the Ni(OH)2 nanowire electrode requires an overpotential of 227 mV to achieve a catalytic reaction of 10 mA / cm 2 The hydrogen production current density is

[0076] like Figure 4 For the oxygen evolution reaction, the Ni(OH)2 nanowire electrode requires an overpotential of 390 mV to drive the catalytic reaction to 50 mA / cm 2 The oxygen production current density.

[0077] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing a three-dimensional network Rh / Ni(OH)2 nanowire composite material, characterized in that: The steps include: (1) adding nickel salt and urea into water in proportion and ultrasonicating to obtain a uniform clear and transparent solution; (2) transferring the clear and transparent solution to a polytetrafluoroethylene-lined reactor, adding a rhodium salt solution, and stirring to obtain a mixture solution; (3) placing the washed nickel foam into the above-mentioned mixture solution and sealing it in a reaction kettle, heating it for hydrothermal reaction, and after the reaction, taking out the nickel foam after reaction, washing it, and drying it to obtain a Rh / Ni(OH)2 nanowire network composite material.

2. The preparation method according to claim 1, characterized in that In step (1), the nickel salt refers to one of nickel chloride, nickel nitrate or nickel sulfate.

3. The preparation method according to claim 1, characterized in that: In step (2), the rhodium salt refers to one of rhodium chloride, rhodium chloride hydrate, or rhodium nitrate.

4. The preparation method according to claim 1, characterized in that: In steps (1) and (2), the usage ratio of nickel salt, urea and rhodium salt is: 0.291-2.910g: 0.601-6.010g: 0.5-25mg.

5. The preparation method according to claim 1, characterized in that: In step (2), the concentration of the rhodium salt solution is 10-100 mg / mL.

6. The preparation method according to claim 1, characterized in that: In step (3), the size of the nickel foam is 1-3 mm in thickness and 1 cm×2 cm-4 cm×5 cm in area.

7. The preparation method according to claim 1, characterized in that: In step (3), the temperature of the hydrothermal reaction is 90-150° C., and the reaction time is 6-24 hours.

8. The preparation method according to claim 1, characterized in that: In step (3), washing is performed by washing with water; and drying is performed by drying at a temperature of 60°C.

9. A three-dimensional network Rh / Ni(OH)2 nanowire composite material, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the three-dimensional network Rh / Ni(OH)2 nanowire composite material according to claim 9 for electrocatalytic water decomposition to produce hydrogen.